Laser in Ophthalmology and Neurosurgery - Zahraa Mohammed Kazem Nasser; Luma kareem hafedh sabr; Ameer Ali Hashim Salman; Huda Razak Khali Hussain; Bander Falaah Satm Khinjar (Genius Journals, 2024)
It was concluded that the laser is today's weapon towards technological progress in the field of medicine and other fields. The laser can treat the most dangerous diseases and reach the most accurate areas of the body, and by means of it the surgery ends without blood and without pain, and the patient can resume his work immediately after the operation
Keywords: phthalmology; Neurosurgery; blood